Arjuna draws an arrow - Mahabharata - 59 - Brig Ajai Singh (2022)
[ Arjuna is shown drawing an arrow from his quiver in the midst of the Mahabharata war. Hanuman can be seen sitting atop his chariot, providing protection to it. ] [ Image courtesy: Brig A.P. Singh - www.collectingmoment.in ]